USE OF HATE SPEECH AS A POLITICAL STRATEGY DURING ELECTION CAMPAIGN: A THREAT TO DEMOCRACY - Panda, Srutakirti; Mohanty, Madhubrata (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The use of hate speech for political purposes during election campaigns is a disturbing phenomenon that threatens the democratic foundations of the societies. Politicians utilize divisive rhetoric to mobilize voters and supporters by inciting fear, animosity and polarization related to race, religion, ethnicity or gender by using hate speech as a political weapon. The current study analyses contemporary electoral campaign patterns across many democracies, focusing on the correlation between hate speech and voter manipulation and how these factors erode democratic principles of participation, equality and informed expression. A thorough review is conducted on the function of media and social media platforms in magnifying these messages, so generating echo chambers that distort the public discourse. In this light the present paper intends to assert that the unfettered propagation of hate speech undermines political culture and erodes public trust in democratic institutions, highlighting its legal, ethical and social implications as a pressing challenge necessitating policy intervention and increased societal awareness.